2022
DOI: 10.1021/acscatal.2c01746
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Methanol Dehydration Catalyzed by Al8O12 Nodes Assisted by Linker Amine Groups of the Metal–Organic Framework CAU-1

Abstract: Elucidation of catalytic sites and mechanisms of reactions on metal oxides is hindered by the complexity and heterogeneity of the surfaces. In contrast, the metal oxide cluster nodes of metal–organic frameworks (MOFs) have well-defined, essentially molecular structures that provide excellent platforms for understanding catalytic reactions in depth. We report an experimental and density functional theory (DFT) investigation of methanol dehydration on the Al8O12 nodes of the MOF CAU-1, presenting catalyst perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The presumably associative ligand exchange mechanism could be a proxy not only for solvent-induced structural breakdown of MOFsfor example certain Zr MOFs containing m 2 -OH ligands at their SBUs are known to be sensitive to CH 3 OH [80][81][82] but also a potential mechanism for small molecule activation, as similar bridging methoxide units at the SBUs of related MOFs have been implicated in catalytic mechanisms. 83 In addition, formation of terminal Zr-OCH 3 units at defect sites in Zr MOFs is implicated in their CH 3 OH activation for further functionalisation, 84 while the presence of m 2 -OCH 3 in the SBUs of GUF-1 could explain changes in physical properties observed when related MIL-53 analogues are directly synthesised in CH 3 OH. 85,86 Our bulk scale pressure measurements identied a low level (∼2%) pore-located impurity in the samples, which we have not currently identied, but whose isotopic enrichment conrms its origin in the 13 CH 3 OH used to induce reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The presumably associative ligand exchange mechanism could be a proxy not only for solvent-induced structural breakdown of MOFsfor example certain Zr MOFs containing m 2 -OH ligands at their SBUs are known to be sensitive to CH 3 OH [80][81][82] but also a potential mechanism for small molecule activation, as similar bridging methoxide units at the SBUs of related MOFs have been implicated in catalytic mechanisms. 83 In addition, formation of terminal Zr-OCH 3 units at defect sites in Zr MOFs is implicated in their CH 3 OH activation for further functionalisation, 84 while the presence of m 2 -OCH 3 in the SBUs of GUF-1 could explain changes in physical properties observed when related MIL-53 analogues are directly synthesised in CH 3 OH. 85,86 Our bulk scale pressure measurements identied a low level (∼2%) pore-located impurity in the samples, which we have not currently identied, but whose isotopic enrichment conrms its origin in the 13 CH 3 OH used to induce reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of computational studies of chemical processes catalyzed by MOFs have provided structural, thermodynamic, and mechanistic insights. Herein, we present theoretical calculations that address the following five fundamental questions relevant to the catalytic mechanism of NO release from GSNO at an active site of a Cu-BTTri MOF catalyst. First, what constitutes a minimal functional model for the MOF, the GSH, and the GSNO that will enable meaningful computational studies?…”
Section: Introductionmentioning
confidence: 99%
“…The dehydration reactions of methanol, ethanol, and tert -butyl alcohol , have been used to characterize the catalytic sites of MOFs that incorporate Zr 6 O 8 nodes, a large family typified by the well-investigated UiO-66. This MOF is appealing in prospect for catalytic applications because it has (relatively) high stability (being reported to retain its crystalline structure at temperatures as high as 400 °C) , and includes members offering a wide range of pore sizes. ,, The results of experiments characterizing the catalytic properties of UiO-66 have shown that changes in the composition of the node ligands, including hydroxyl, aqua, and alkoxides, ,,, and even the linkers, affect the catalyst performance.…”
Section: Introductionmentioning
confidence: 99%
“…14−16 This MOF is appealing in prospect for catalytic applications because it has (relatively) high stability (being reported to retain its crystalline structure at temperatures as high as 400 °C) 15,17 and includes members offering a wide range of pore sizes. [14][15][16]18,19 The results of experiments characterizing the catalytic properties of UiO-66 have shown that changes in the composition of the node ligands, including hydroxyl, aqua, and alkoxides, 5,6,12,13 and even the linkers, 7 affect the catalyst performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation